1993
DOI: 10.3109/15513819309048227
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Granulosa Cell Tumor of the Testis: A Comparative Immunohistochemical Study with Normal Infantile Gonads

Abstract: This study concerns the nature of two different cell populations in a juvenile granulosa cell tumor (GCT) of the infantile testis. Immunohistochemical features of the tumor were compared with those of normal infantile testes (six cases) and ovaries (six cases). The testicular neoplasm showed follicles, cysts and solid nodules composed of an internal layer of polyhedral cells that expressed cytokeratin and vimentin. Most of the follicles and nodules were surrounded by an external layer of spindle cells that rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…[5][6][7][8][9][10][11][12] We have encountered patterns and cytologic features that have not been described in the literature or only to a minimal degree, which may potentially cause confusion with other neoplasms, most often yolk sac tumor (YST) or, rarely, other sex cord stromal tumors. 13,14 We therefore undertook a comprehensive morphological analysis of testicular JGCT to highlight not only the classic features but also unusual aspects and those useful in differentiating it from other neoplasms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10][11][12] We have encountered patterns and cytologic features that have not been described in the literature or only to a minimal degree, which may potentially cause confusion with other neoplasms, most often yolk sac tumor (YST) or, rarely, other sex cord stromal tumors. 13,14 We therefore undertook a comprehensive morphological analysis of testicular JGCT to highlight not only the classic features but also unusual aspects and those useful in differentiating it from other neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…Sixty-seven (96%) were punctuated by variably-sized and shaped follicles (Figs. 2, 3B, [4][5][6] containing basophilic material (21%), eosinophilic material (44%), or both (35%). Mixed follicular and solid patterns occurred in 55 cases (79%) with follicular predominance in 33 (47%) and solid predominance in 22 (32%).…”
Section: Pathologic Featuresmentioning
confidence: 99%
“…[44][45][46][47][48][49] The better known yolk sac tumor of the testis of young boys peaks after 6 months of age. 8 The tumors are uncommon in older children and are exceptionally rare in adults.…”
Section: Testicular Juvenile Granulosa Cell Tumormentioning
confidence: 99%
“…They contain desmin [17]. And it has been reported that the expression pattern of desmin may be related to the myoid cell differentiation in the developing testis [1,7,11,14,18,20]. Fibronectin is localized to the basement membrane of the testicular cord.…”
Section: Discussionmentioning
confidence: 99%
“…Since desmin, one of intermediate filaments, is expressed in smooth muscle cells and mesenchymal cells [12,21], it has been used as a marker to investigate the differentiation of mesenchymal cells [18], interstitial cells [5], and myoid cells [5,7,13,18,19,23] in mammalian species. On the other hand, it is well known that fibronectin is localized to the basement membrane of the testicular cord [8,15].…”
Section: Methodsmentioning
confidence: 99%